The Effect of Parental Divorce on Children’s Mental Health - Trenggono, Aisha; Achdiani, Yani; Nastia, Gina (Balai Publikasi Indonesia, 2025)
Divorce is a condition where the relationship between husband and wife ends, which can be caused by various factors, one of which is poor communication. Divorce not only affects the couple but also has a negative impact on the mental health of children in the family. This study aims to understand the effects of divorce on children's mental health using a literature review method. Data were obtained through the analysis of various sources such as books, journals, and relevant research reports. The results of the study indicate that divorce can cause children to experience stress, trauma, feelings of loneliness, withdrawal, and concentration difficulties in learning. Furthermore, children from divorced families tend to have lower academic performance and struggle to build social relationships. In conclusion, parental divorce has a significant impact on children's mental health, which can affect their emotional and social development in the future. Therefore, it is crucial for parents and relevant parties to provide psychological support to help children cope with this situation more effectively.